LEGAL ASPECTS OF COMPENSATION REQUIREMENTS OF ENVIRONMENTAL DAMAGE AS A RESULT OF THE WAR OF THE RUSSIAN FEDERATION IN UKRAINE - Mykulets, Vitalii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Aim: is to establish the readiness of Ukrainian environmental legislation to provide legal compensation for environmental damage as a result of the russian federation war in Ukraine. It is necessary to achieve this aim because: 1) one can need to determine the content of the concepts «environmental damage» and «environmental damage during the war», 2) to determine the content of analysis of Ukrainian environmental legislation for the possibility of providing appropriate compensation. Research methods: we used general theoretical and analytical methods in combination with an integrated approach. Results: it is shown at the theoretical level of the study the shortcomings of the Ukrainian legal position concerning the provision of compensation for environmental damage due to russian aggression. It is proposed to define the concepts of «environmental damage» and «environmental damage during the war» at the level of the relevant Law. The validity of reflecting the position at the level of the law is defended. Discussion: russia's invasion of Ukraine in a short period of time has made a significant amount of environmental risks and real problems. The current facts and the position of the Ukrainian society made necessary the problems of providing compensation for environmental damage due to the russian federation war in Ukraine. However, in the future there may be some complications in this matter, as the definition of «environmental damage» is still controversial not only among Ukrainian scientists, but also absent at the level of national legislation. Taking into account the complex and inefficient practice of applying the norms of international humanitarian law (in particular with regard to environmental protection), it is logical to reconsider this situation. In particular, to bring the conceptual range of national environmental legislation in line with the content of international acts.